(untitled) (Transport systems and technologies, 2018)
The article deals with the load stresses in the strain gage bottom edges as one of the principal parameter of the rolling stock impact on the track. The study of the available research on this subject resulted into the fact that the determination of the maximum possible values of load stresses in strain gage bottom edges and their variation behavior in dependence of the running speed on the curved tracks continue to be relevant for introduction of high-speed running The aim of the work is to define the dependence of the load stresses values in strain gage bottom edges under various speeds of a passenger car running on curved tracks. Diagrams of maximum possible load stresses versus running speed of a passenger car on curved tracks of 419m, 906m, and 1530m radiuses are plotted. The values of the maximum possible load stresses, generating in inner and outer bottom edges of strain gages in dependence of the speed were determined. It was found out that load stresses in the strain gage bottom edges increase with the speed rise and shortening of a curve radius, upon that the increase behavior is of random nature.